Butyrate suppresses experimental necrotizing enterocolitis–induced brain injury in mice - Martinez, Maribel; Yu, Wei; Menden, Heather L.; Lei, Tianhua; Monaghan-Nichols, Paula; Sampath, Venkatesh (Frontiers in Pediatrics, 2023)
Background: Necrotizing enterocolitis (NEC) is a devastating disease in premature infants, and 50% of infants with surgical NEC develop neurodevelopmental defects. The mechanisms by which NEC-induced cytokine release and activation of inflammatory cells in the brain mediate neuronal injury, and whether enteral immunotherapy attenuates NEC-associated brain injury reman understudied. Based on our prior work, which demonstrated that experimental NEC-like intestinal injury is attenuated by the short chain fatty acid, butyrate, we hypothesized that NEC-induced brain injury would be suppressed by enteral butyrate supplementation. Methods: Standardized NEC mouse model (enteral formula feeding, lipopolysaccharide (LPS) and hypoxia) was used. Mice were randomized into groups: control, NEC, butyrate pre-treated NEC, and butyrate control. NEC scoring (1-4 with 4 representing severe injury) was performed on ileal sections using a validated scoring system. Intestinal and brain lysates were used to assess inflammation, pro-inflammatory signaling, and apoptosis. Results: NEC-induced intestinal injury was attenuated by butyrate supplementation. NEC-induced microglial activation in the cerebral cortex and hippocampus were suppressed with butyrate. NEC increased numbers of activated microglial cells but decreased the number of oligodendrocytes. Butyrate pre-treatment attenuated these changes. Increased activation of pro-inflammatory TLR signaling, cytokine expression, and induction of GFAP and IBA1 in the cerebral cortex observed with NEC was suppressed with butyrate. Conclusion: Experimental-NEC induced inflammation and activation of microglia in several regions of the brain, most prominently in the cortex. NEC-induced neuroinflammation was suppressed with butyrate pre-treatment. Addition of SCFA’s to diet may be used to attenuate NEC-induced intestinal injury and neuroinflammation in preterm infants.